Research and development of animals' flocking behaviour - Tan, Kenneth Kang Wei (2014)
Flock commonly refers to a group of animals, where animals form groups among themselves and operate in their flock groups. Through the use of flocking simulation, many researches/applications are able to achieve the result relatively fast when compared to manual work. In light of this, Flocking Animation and Modelling Environment (FAME) is being developed aiming to provide users with a better control over flocking behavior.